KNOWLEDGE, ATTITUDES AND UPTAKE OF COVID-19 VACCINATIONS AMONG NURSES AT MBARARA REGIONAL REFERRAL HOSPITAL - Kanyemibwa, Margaret; Betunga, Benjamin; Meble, Kasande; Otwine, Anne Tweheyo (Student’s Journal of Health Research Africa, 2023)
Background. Vaccination is the most important and reliable public health measure and the most effective strategy for protecting the population from COVID‐19. Much as vaccines are present, there is low uptake due to their low availability, poor attitudes, and low levels of knowledge among the population due to hesitancy.Low vaccination uptake poses the population and nurses at risk of acquiring the disease and of individuals developing complications of the same disease compared to vaccinated communities. Methodology. The study had a hospital-based cross-sectional descriptive design, as data were collected from participants at one point in time. Data were collected using a questionnaire administered to 138 randomly sampled nurses at the Mbarara Regional Hospital. Results. The majority of the nurses (67.4%) had heard of COVID-19 vaccination, and 85.5% had been vaccinated. The majority believed that vaccination was safe, with some side effects (87.0%), 67.4% had good knowledge about COVID-19 vaccination, and 32.6% had moderate knowledge about vaccination. The majority (73.3%) of the participants had a positive attitude toward vaccination and 26.8% had a negative attitude towards vaccination. Conclusion. This study revealed that the majority of nurses generally had good knowledge of COVID-19 vaccination. However, in the context of a pandemic, vaccine hesitancy is a major barrier to the implementation of vaccination campaigns. To maintain the benefits of vaccination programs, understanding and addressing vaccine hesitancy are crucial to their successful implementation. Recommendation. The government, through the Ministry of Health, should strengthen the COVID-19 vaccination awareness campaign, focusing on people living in rural areas by making relatively more detailed information readily available through easily accessible communication channels, such as local radio stations and health education programs at health facilities and community health outreaches.